Incidence of postpartum infections and outcomes associated with antibiotic prophylaxis after normal vaginal birth - Sirilak, Thitipong; Kanjanarat, Penkarn; Nochaiwong, Surapon; Katip, Wasan (Frontiers in Medicine, 2022)
Antibiotic consumption accounted for approximately 15–20% of total drug costs in Thailand. From 2017–2018, 24.86% of Thai women who experienced vaginal delivery during normal term labour received antibiotics for postpartum infection. The Thai national practice guidelines set the target use of antibiotic prophylaxis in women following vaginal delivery of normal term labour to be no more than 10%. This study aimed to determine the incidence of postpartum infections and the outcomes and factors associated with antibiotic prophylaxis in women following vaginal delivery. The prospective cohort study was collected from 909 eligible patients who delivered infants in 7 secondary hospitals in Chiang Mai from July 2020 to February 2021. Antibiotic prescribing data and infections in women experiencing vaginal delivery during normal term labour were collected. The incidence of postpartum infections was calculated at 2 periods, 48 hours and 6 weeks, after labour. Factors associated with the prescription of antibiotic prophylaxis in vaginal delivery were analysed using multivariate logistic regression. The results showed that the prevalence of antibiotic prescribing was 12.87 % in a cohort of 117 patients. Postpartum infection was reported in 3 of 117 patients with antibiotics prophylaxis and 11 of 792 without antibiotics, with no statistically significant difference (RR: 1.04, 95% CI: 0.26–4.14; p=0.956). Postpartum hygiene self-care practices were collected in the 6th week. The results found that there were no statistical differences in mean scores for all questions on postpartum hygiene self-care practices between the infected and non-infected groups (p-value > 0.05). One of the factors associated with antibiotic prophylaxis was 3th – 4th degree of tear and episiotomy (OR: 7.72, 95% CI: 1.13 – 52.75; p=0.037 and OR: 2.41, 95% CI: 1.24 – 4.70; p= 0.010, respectively). There was no significance difference in postpartum infection among patients receiving antibiotic and those who did not receive antibiotics. 3rd – 4th degree of tear and episiotomy were significantly factors related to antibiotic prophylaxis in women with vaginal delivery after labour. This study supports practice guidelines and helps healthcare team to be assured on the use of antibiotics in no more than 10% of women experiencing normal vaginal delivery.